Hydrodynamic characterization of planing surfboards using CFD - D`Ambrosio, D. (Proceedings, 2020)
Computational fluid dynamics is recently being considered as an interesting tool to predict and analyze surfboards` hydrodynamic characteristics for the purpose of optimizing the design. In this paper we define a systematic methodology that could be used to measure forces and moments exerted by the fluid on the surfboard. We define a "surfboard attitude" matrix, for instance varying the angle of attack and the tip surfacing height, and we fill it with values of drag, lift and moment. With these data, we can calculate the position of the center of pressure and analyze static equilibrium conditions in the presence of external forces that represent the weight of a surfer.